Handbook of sea-level research - Ian Shennan; Shennan, Ian.; Long, Antony; Horton, B. P. (NewJersey Wiley, 2015)
"This book will cover all aspects of modern sea-level studies, with a focus on the most robust scientific approaches and techniques"--
Includes bibliographical references and index.
Keywords: Sea-level; Climatic changes; SCIENCE / Earth Sciences / Oceanography